The Role of Information Technology in Improving Organizational Learning A Field Study at Tishreen University"" - البهلول, علي (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to study the role that information technology plays in improving the level of organizational learning in its two dimensions (single and dual loop learning) at Tishreen University. The researcher relied on the analytical descriptive approach, since it was distributed (222) questionnaire to a sample of employees at Tishreen University, (159) questionnaires were retrieved, valid for analysis (122). To test the hypotheses of the study, the researcher used the Student T test for one sample, as well as Pearson's correlation coefficient. The research found a decrease in the level of information technology is used at Tishreen University and a decrease in the level of organizational learning in its two dimensions (single and dual loop learning) at the university. The research also found a significant relationship between information technology and organizational learning at Tishreen University, and thus there is a role for information technology in improving the level of organizational learning. The research concluded with a set of recommendations and proposals related to the need to pay attention to the information technology infrastructure, using of modern technological methods in transferring and sharing knowledge, in addition to enhancing the organizational learning process in higher education institutions, and other recommendations that would contribute positively to the role of information technology in improving organizational learning process.